Analisis Strategi Pengelolaan Penjualan Kredit Pada PT Bronson Prima Industri Cabang Medan - Melwinda Laia; Husni Mubarak (CIVITAS: Jurnal Studi Manajemen, 2022)
This study discusses the analysis of credit sales management strategies at Pt Bronson Prima Industri Medan Branch. The problem formula in this research is How to Analyze the strategy of managing credit sales at PT Bronson Prima Industri Medan branch. The purpose of this study was to determine the credit sales management strategy implemented by PT Bronson Prima Industri Medan branch. This research is a qualitative descriptive study. Primary data is needed as a tool to collect information in the form of organizational structure, a brief history of PT. Bronson Prima Industri. The results of this study are: 1. Policy within a maximum credit period of 14 days, credit sales standards at PT Bronson Prima Industri also apply an assessment of the business prospects run by customers and owned resources. Terms of credit sales include KTP, NPWP, and credit application forms. 2. Credit management implemented by PT Bronson Prima Industri Medan branch includes limits on the amount of credit sales, credit ceiling provision, terms of credit repayment, provisions on limits on the number of loans, and the policy on collecting receivables.